Mixed Intervillositis in SARS-CoV-2 Infection Associated with Fetal Death: A Case Report - Boban Gjakov; Darja Kopač; Mateja Vukmanič Pohar; Miha Lučovnik (Case Reports in Obstetrics and Gynecology)
Maternal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been shown in epidemiological studies to be associated with an increased risk of stillbirth. Several histopathologic features of placental SARS-CoV-2 infection have been proposed as potential causes of fetal death. We present a case of an otherwise healthy G3P1 women with mild symptoms of SARS-CoV-2 infection at 23 6/7 weeks of gestation. At 25 2/7 weeks, she presented with signs and symptoms of preterm labor and decreased fetal movements. Fetal death was diagnosed at admission. Placental pathology showed pronounced placental mixed intervillositis. Inflammatory infiltrate caused extreme narrowing of intervillous space leading to placental malfunction and fetal death. Placental tissue SARS-CoV-2 infection was confirmed by positive immunohistochemistry staining of syncytiotrophoblasts with spike protein antibody. The case presented suggests that SARS-CoV-2 associated inflammatory placental changes pose an elevated risk for the fetus.